Growth Performance and Lipid Profile of Broiler Chickens Fed Fermented Millet Stalks - Halliru MI; Yaradua AI; Nasir A; Kankia IH; Matazu KI; Usman A; Sada AA; Suleiman ZA; Labaran IA; Abbas A; Mukhtar F; Kabir M. (Archives of Current Research International, 2025)
High cost of feed production has been a persistent thorn in the flesh on the Nigerian poultry production sector. The price of maize a key source of carbohydrate in feed formulation is above board. The study revealed the potential of using Aspergillus niger fermented millet stalk (FMS) as maize replacement in broiler feed formulation. Millet stalk sample was fermented using Aspergillus niger at pH 7 and temperature of 350C for 5 days to enhance its nutritional composition for inclusion in broiler feed formulation. Five diets were prepared with five different levels of FMS as maize replacement, namely 0% FMS (D1) 25% FSM (D2), 50% FMS (D3), 75% FMS (D4), and 100% (D5). The experimental Broilers were given the formulated diet for eight consecutive weeks. The Broilers were subjected to growth performance and lipid profile assessment. The mean weight, average daily weight gain and average weight gain of the studied chicken were highest in group D3 (2055g, 48.93g, 1630g) and least in group D4 (1741g, 41.45g, 1343g), the gain to feed ratio was highest in group D3 (2.78g) and least in group D5 (1.30g). The study findings demonstrated that FMS had a significant (p<0.05) effect on average body weight gain, feed conversion ratio and growth rate. Significant influences were not observed for all the lipid profile parameters. The findings underscore the viability of fermented millet stalk as a sustainable and cost-effective substitute for maize in poultry diets.